Divine Revelation in the Pentateuch - Arnold, Bill T. (The Asbury journal, 2018)
Studies of divine revelation in the Old Testament rightly focus on Israel’s encounter with God at Mount Sinai recorded in Exodus 19-24 (and interpreted in Deuteronomy 4). But theologians often neglect the earlier expressions of divine self-disclosure, which hold potential to enrich our understanding of this essential Christian doctrine. This paper investigates the ancestral narratives of Genesis (especially Gen 12:7 and 17:1) and the appearance of YHWH to Moses at the burning bush (Exod 3-4), in order to gain a more complete perception of divine revelation in the Pentateuch, which then offers contributions to Christian theologizing about the doctrine of revelation generally. This paper was presented to the Asbury ARP Interdisciplinary Colloquium for 2017 in celebration of the decennial of the Amos endowment, marking the beginning of the Asbury PhD (Biblical Studies) program. This paper was presented in memory of Mr. Paul S. Amos and in honor of Mrs. Jean R. Amos.